A companion to American art - Davis, John, 1961 September 24-; Greenhill, Jennifer A., 1974-; LaFountain, Jason David (Malden, MA : Wiley- Blackwell, 2015)
A Companion to American Art presents 35 newly-commissioned essays by leading scholars that explore themethodology, historiography, and current state of the field ofAmerican art history.
Writing American art history -- Geographies : rethinking Americanness -- Subjectivities -- Art and public culture
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Art, American; ART -- History -- General; Art, American; Electronic books